Associations of 10 dietary habits with breast cancer: a Mendelian randomization study - Wang, Xuyutian; Chen, Lanlan; Cao, Runxiang; Ma, Ruolin; Liu, Yutong; Zhao, Qian; Du, Ye (Frontiers in Nutrition, 2023)
Epidemiological studies have revealed a link between dietary habits and the breast cancer risk. The causality of the association between food consumption and breast cancer requires further investigation. Using Mendelian randomization, we assessed the causal effects of ten dietary habits on the risks of breast cancer and its subtypes (estrogen receptor [ER]+ and ER-breast cancer). We obtained dietary pattern data in 2018 (number of single-nucleotide polymorphisms [SNPs] = 9,851,867) and breast cancer data in 2017(number of SNPs = 10,680,257) from IEU OpenGWAS. Rigorous sensitivity analyses were conducted to ensure that the study results were credible and robust. We identified that genetic predisposition to higher dried fruit intake was linked to a reduced risk of overall breast cancer (inverse variance-weighted [IVW] odds ratio [OR] = 0.55; 95% confidence interval [CI]: 0.43-0.70; p = 1.75 × 10 -6 ), ER+ breast cancer (IVW OR = 0.62; 95% CI: 0.47-0.82; p = 8.96 × 10 -4 ) and ER-breast cancer (IVW OR = 0.48; 95% CI: 0.34-0.68; p = 3.18×10 - 5 ), whereas genetic predisposition to more oily fish intake was linked to a lower risk of ER+ breast cancer (IVW OR = 0.73; 95% CI: 0.53-0.99; p = 0.04). Our findings suggest that a genetic predisposition for dried fruit and oily fish consumption may be protective against breast cancer; however, further investigation is required.